2011
DOI: 10.1016/j.jbusres.2010.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Parental responsiveness and adolescent susceptibility to peer influence: A cross-cultural investigation

Abstract: From a developmental perspective, this research focuses on how parental responsiveness affects adolescent susceptibility to peer influence both directly, and indirectly, through the key elements of adolescent selfconcept (i.e., interdependent self-construal, self-esteem, and self-monitoring). The proposed parent-self-peer model incorporates culture as a moderator. The overarching finding is that in individualist cultures such as Canada, responsiveness reduces susceptibility mainly through an indirect effect by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 55 publications
2
75
2
6
Order By: Relevance
“…The collectivist orientation of Chinese societies is attributed to the influence of Confucianism, with its emphasis on respect for social harmony and protection of the interests of one's in-group (Shafer et al 2007;Su et al 2003;Whitcomb et al 1998). Chinese parents, with high power distance, are more protective of their children, encourage them to respect authority and rules, and obey laws (Tang 1990;Yang and Laroche 2011). These cultural differences echo prior research regarding differences in parental socialization between individualistic and collectivist cultures.…”
Section: Parental Attachmentmentioning
confidence: 57%
See 1 more Smart Citation
“…The collectivist orientation of Chinese societies is attributed to the influence of Confucianism, with its emphasis on respect for social harmony and protection of the interests of one's in-group (Shafer et al 2007;Su et al 2003;Whitcomb et al 1998). Chinese parents, with high power distance, are more protective of their children, encourage them to respect authority and rules, and obey laws (Tang 1990;Yang and Laroche 2011). These cultural differences echo prior research regarding differences in parental socialization between individualistic and collectivist cultures.…”
Section: Parental Attachmentmentioning
confidence: 57%
“…French teens view sharing as egoistic rather than altruistic, and self-oriented rather than other-oriented behavior. French parents encourage adolescents to make independent decisions and (Yang and Laroche 2011). To achieve autonomy from their parents, French adolescents progressively distance themselves from their parents and increasingly rely on their peers.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Similar results were reported by Szeto et al (2009), who compared Canadians and Japanese, and found that the former have significantly higher scores on the Rosenberg selfesteem scale than the latter. Additionally, Yang and Laroche (2010) argued that because Canadian adolescents are armed with a higher level of self-esteem, they are less susceptible to peer influence than their Chinese counterparts.…”
Section: The Social Identity Conceptmentioning
confidence: 99%
“…Adolescents increasingly recognize themselves as distinct entities, behave independently, and individuate themselves from others (Gentina and Chandon 2013;Nuttall and Tinson 2008;Yang and Laroche 2011). This need for individuation involves asserting differentness and expressing uniqueness; thus, we use consumer need for uniqueness (CNFU) (Tian et al 2001) to operationalize this need.…”
Section: Need For Individuation and Ep/rbmentioning
confidence: 99%
“…It is a time of rapid development, emerging independence from parents, and a growing reliance on peer support (Goodrich and Mangleburg 2010;Mangleburg et al 2004;Yang and Laroche 2011). Becoming a member of a peer group and defending one's social position within these groups represent major developmental milestones in adolescence (Steinberg and Morris 2001).…”
Section: Introductionmentioning
confidence: 99%